Remote sensing assessments of consumptive use of agricultural water in Western Slope of Colorado - Vashisht, Amandeep, author; Chávez, José L., advisor; Cabot, Perry E., advisor; Leisz, Stephen J., committee member (Colorado State University. Libraries, 2016)
The Western Slope of Colorado is drained by Colorado River and its tributaries, which are facing increased pressure on their water resources due to prolonged droughts and increasing demands. While water is a limited resource, agriculture uses more than half of the total diverted water in the area. In such a scenario, agricultural water can be a likely supply for water conservation and sharing. The quantification of precise amount of water consumed by agricultural crops, or, consumptive use, is crucial for water sharing under temporary water sharing arrangements like water banks. Remote Sensing is considered as the most feasible method to determine spatial actual crop water use over large areas. A preliminary performance evaluation of ReSET model for daily consumptive water use estimates under energy limiting and water limiting conditions was done. Conserved Consumptive Use estimates from plots replicating historical (full irrigation) and operational water bank (reduced irrigation) conditions were made on a monthly basis. In addition, crop growth stage information for grass and alfalfa pastures of the Western Slope was determined using Landsat and Sentinel satellites. An empirical relation between vegetation index (VI) and crop coefficient (Kc) was developed for use with reflectance-based crop coefficient approach. Lastly, reflectance-based approach for grass and alfalfa pastures was evaluated with ReSET-derived daily estimates of crop consumptive use.
Keywords: pastures; ReSET; water sharing agreements; feflectance-based crop coefficient approach; evapotranspiration; satellites